How natural resources affect financial development? Fresh evidence from top-10 natural resource abundant countries. (June 2022) - Han, Jingwei; Raghutla, Chandrashekar; Chittedi, Krishna Reddy; Tan, Zhixiong; Koondhar, Mansoor Ahmed
Abstract: This study is to examine the impact of natural resources, economic growth, export diversity and inflation on financial development in top-10 natural resource abundant countries, spanning the period of 1990–2020. The empirical outcomes show that natural resources, economic growth, export diversity, inflation and financial development have long-run equilibrium relationship. Further, export diversity, economic growth and inflation increase financial development but natural resources reduce financial development in natural resource abundant countries. Furthermore, panel causality results show a unidirectional causality moving from financial development to export diversity and inflation. The empirical results offer new insights for policy makers to protect their natural resources for the betterment of financial development in top-10 natural resource abundant countries. Highlights: Examine the impact of natural resources, economic growth, export diversity and inflation on financial development. This study analyzed for top 10 natural resource abundant countries from 1990 to 2020. Natural resources, economic growth, export diversity, inflation and financial development have long-run equilibrium relationship. Unidirectional causality moving from financial development to export diversity and inflation.